2018
DOI: 10.1007/s10103-018-2454-4
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation (PBM) therapy at 904 nm mitigates effects of exercise-induced skeletal muscle fatigue in young women

Abstract: Muscle fatigue is a process influenced by several mechanisms such as concentration of metabolic substrates, changes in blood flow, and increases in reactive oxygen species that impair contractile muscle function. In this context, photobiomodulation has been investigated for preventing muscle fatigue, with reports of positive effects on muscle performance. This study aimed to investigate the effects of 904-nm LASER photobiomodulation on rectus femoris muscle performance in young women. Eighteen young women part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 36 publications
0
33
0
1
Order By: Relevance
“…A small number of studies of the neuroprotective action of lycopene have appeared. In animal studies, for example, Lei and colleagues 176 reported that pretreatment of rats reduced cell death and functional loss in a model of stroke, the effect involving the NF erythroid 2/heme-oxygenase pathway; Yin and colleagues 177 reported that cognitive impairment induced in rats by consumption of fructose is ameliorated by lycopene administration; Prakash and Kumar 178 and Yi and colleagues 179 reported that lycopene reduces mitochondrial dysfunction in toxin-induced models of dementia and 157 Pinto et al, 158 Toma et al 159…”
Section: Lycopene (Tomatoes and Watermelon)mentioning
confidence: 99%
“…A small number of studies of the neuroprotective action of lycopene have appeared. In animal studies, for example, Lei and colleagues 176 reported that pretreatment of rats reduced cell death and functional loss in a model of stroke, the effect involving the NF erythroid 2/heme-oxygenase pathway; Yin and colleagues 177 reported that cognitive impairment induced in rats by consumption of fructose is ameliorated by lycopene administration; Prakash and Kumar 178 and Yi and colleagues 179 reported that lycopene reduces mitochondrial dysfunction in toxin-induced models of dementia and 157 Pinto et al, 158 Toma et al 159…”
Section: Lycopene (Tomatoes and Watermelon)mentioning
confidence: 99%
“…Two participants withdrew due to factors not related to the study. Sample size calculation for an F -test was performed using the software G ∗ Power (Axel Buchner, Version 3.0.1; Düsseldorf, Germany) and was based on previous studies that analyzed the effects of laser PBM on the number of repetitions performed ( Leal Junior et al, 2009 ) and RPE ( Toma et al, 2018 ). Based on a statistical power (1 − β) of 0.95, a moderate effect size (0.65) ( Leal Junior et al, 2009 ; Toma et al, 2018 ), and an overall level of significance of 0.05, at least 12 participants were required for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Sample size calculation for an F -test was performed using the software G ∗ Power (Axel Buchner, Version 3.0.1; Düsseldorf, Germany) and was based on previous studies that analyzed the effects of laser PBM on the number of repetitions performed ( Leal Junior et al, 2009 ) and RPE ( Toma et al, 2018 ). Based on a statistical power (1 − β) of 0.95, a moderate effect size (0.65) ( Leal Junior et al, 2009 ; Toma et al, 2018 ), and an overall level of significance of 0.05, at least 12 participants were required for this study. The inclusion criteria were the following: (i) aged 18–30 years, (ii) classified as eutrophic [i.e., body mass index (BMI) range, 18–25 kg/m 2 ], and (iii) classified as low risk for vigorous exercising and testing, according to criteria proposed by the American College of Sports Medicine ( Ferguson, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PBM has been shown to improve the general health and resilience of cells and tissues. The effect of PBM to improve mitochondrial metabolism and ATP generation leads to increased muscle strength and performance in sports and athletics [58,59] and to reduced muscle wasting and degeneration in animal and cell culture models [60][61][62]. This makes it a candidate for treatment of COVID-19 cases under respiratory distress.…”
Section: Photobiomodulation Therapy and General Healthmentioning
confidence: 99%